2015
DOI: 10.1183/13993003.01148-2015
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea in the general population: highly prevalent but minimal symptoms

Abstract: The aim was to assess the prevalence of obstructive sleep apnoea (OSA) as defined by an apnoea-hypopnea index (AHI) ⩾15 in the middle-aged general population, and the interrelationship between OSA, sleep-related symptoms, sleepiness and vigilance.A general population sample of 40-65-year-old Icelanders was invited to participate in a study protocol that included a type 3 sleep study, questionnaire and a psychomotor vigilance test (PVT).Among the 415 subjects included in the study, 56.9% had no OSA (AHI <5), 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
132
2
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(149 citation statements)
references
References 35 publications
9
132
2
6
Order By: Relevance
“…Another population-based study performed in Iceland found that approximately 20% of subjects had moderate to severe OSA and were largely asymptomatic. 11 Together, these studies suggest that the cutoffs for treatment of OSA may need to be adjusted further upward from the current AHI cutoff of 15. 17 In that context, ruling out severe OSA in a general population setting may be more clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another population-based study performed in Iceland found that approximately 20% of subjects had moderate to severe OSA and were largely asymptomatic. 11 Together, these studies suggest that the cutoffs for treatment of OSA may need to be adjusted further upward from the current AHI cutoff of 15. 17 In that context, ruling out severe OSA in a general population setting may be more clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Second, OSA subjects in the general population are usually asymptomatic or have unrecognized symptoms, meaning they are less likely to present to a healthcare provider for further evaluation. 11 Hence, screening questionnaires could be particularly useful in risk stratifying large numbers of subjects in an unselected community-based population for further diagnostic testing.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study by ARNARDOTTIR et al [1], no association was found between sleepiness and OSA, whereas an effect on performance was found only in those with an AHI ⩾30. This is consistent with other population samples that have reported that only one out of five people with OSA complain of sleepiness [18][19][20].…”
mentioning
confidence: 44%
“…ARNARDOTTIR et al [1] from the University Hospital of Iceland studied a large general population sample of middle-aged individuals using polysomnographic sleep recordings, questionnaires and the psychomotor vigilance test (PVT). Of the 415 subjects, 12.5% had moderate obstructive sleep apnoea (OSA; AHI between 15 and 30), 2.9% had severe OSA (AHI ⩾30), and 3.6% were already diagnosed and treated for OSA.…”
mentioning
confidence: 99%
“…Obstructive sleep apnoea syndrome (OSA) is highly prevalent with recent epidemiological reports indicating prevalence for moderate or severe sleep disordered breathing (SDB) of up to 50% in the general male population, although the prevalence of a clinically significant syndrome is considerably less (1,2). Cardiovascular co-morbidity is also common among patients with OSA, and many reports have indicated an independent relationship between OSA and various cardiovascular diseases, especially systemic hypertension (3).…”
mentioning
confidence: 99%